2017
DOI: 10.1111/joim.12696
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of graft‐versus‐host disease increases mortality after umbilical cord blood transplantation for acute myeloid leukaemia: a report from Eurocord and the ALWP of the EBMT

Abstract: Background The efficacy of umbilical cord blood transplantation (UCBT) as treatment for acute myeloid leukaemia (AML) relies on immune‐mediated graft‐versus‐leukaemia effects. Previous studies have suggested a strong association between graft‐versus‐host disease (GVHD) occurrence and graft‐versus‐leukaemia effects after allogeneic hematopoietic cell transplantation. Methods Here, we evaluated the kinetics of relapse rate in correlation with GVHD occurrence after UCBT. The kinetics of relapse rate over time in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…Our study revealed a high incidence of grade III-IV acute GVHD in CBT recipients (15%). A recent study from our group observed that the low incidence of acute GVHD associated with CBT is limited to CBT patients receiving ATG in the conditioning regimen (47). In concordance with this observation, the incidence of grade III-IV acute GVHD in our study was similar to what has been reported by the Seattle (18%; ref.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed a high incidence of grade III-IV acute GVHD in CBT recipients (15%). A recent study from our group observed that the low incidence of acute GVHD associated with CBT is limited to CBT patients receiving ATG in the conditioning regimen (47). In concordance with this observation, the incidence of grade III-IV acute GVHD in our study was similar to what has been reported by the Seattle (18%; ref.…”
Section: Discussionsupporting
confidence: 92%
“…[9][10][11] Despite the rapid growth of T cell replete HLA-haploidentical transplantation, 12 umbilical cord blood transplantation (CBT) has remained an alternative option for patients with high-risk acute leukemia without an HLA-identical sibling donor. [13][14][15][16][17][18] During the last decade, several reports have highlighted the negative impact of detectable measurable residual disease (MRD) at transplantation, on transplantation outcomes in patients transplanted from either HLA-matched related or unrelated donors, as well as in those given cells from HLA-haploidentical donors. [19][20][21][22][23][24][25] This remained true in patients in second complete remission (CR) at transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…While this could be due in part to the relatively high incidence of graft failure observed, we cannot rule out that the frequent use of ATG in our cohort (41%) significantly contributed to this finding. Indeed, previous studies have evidenced than in vivo T-cell depletion had a profound negative impact on immune recovery in CBT recipients and increased NRM in patients with de novo AML [28][29][30]. However, there was no significant association between ATG and NRM in this cohort of patients.…”
Section: Discussionmentioning
confidence: 52%
“…Two-year incidences of relapse and of NRM were 29% (95% CI, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and 39% (95% CI, 31-48), respectively. The figures were 25% (95% CI, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] and 35% (95% CI, 25-45), respectively, in patients in CR1, versus 36% (95% CI, 22-49, P = 0.06) and 49% (95% CI, 33-62, P = 0.03), respectively, in patients with active disease at transplantation ( Fig. 1).…”
Section: Relapse and Nonrelapse Mortalitymentioning
confidence: 99%
See 1 more Smart Citation